Creating a NIRS (Near Infrared Spectroscopy) database for tropical forages - Cardoso Arango, Juan Andrés (Bioversity International and the International Center for Tropical Agriculture, 2022)
Near-Infrared Reflectance Spectroscopy (NIRS) is a non-destructive analytical technique that uses the near-infrared region of the electromagnetic spectrum to analyze the chemical composition of a material. There are already several open NIRS databases available for different types of materials, such as food, feed, and agricultural products. However, an open NIRS database specifically focused on tropical forages is not yet available.